HUBUNGAN ANTARA PEMAHAMAN SEJARAH LOKAL DENGAN SIKAP TOLERANSI MAHASISWA SEJARAH IKIP-PGRI PONTIANAK - Sahid Hidayat; Haris Firmansyah; Fivi Irawani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This study aims to determine the relationship between the understanding of local history with tolerance education students history IKIP PGRI Pontianak. The variables in this study are as follows, namely: 1) The independent variables, namely